Predicting and implications of target volume changes of brain metastases during fractionated stereotactic radiosurgery. (January 2020) - Hessen, Eline; Nijkamp, Jasper; Damen, Pim; Hauptmann, Michael; Jasperse, Bas; Dewit, Luc; Lutkenhaus, Lotte; Lamers, Emmy; van der Heide, Uulke; Damen, Eugène; Hanssens, Patrick; Borst, Gerben
Highlights: Patients received a new MRI during fractionated SRS for brain metastases. The observed target volume changes deteriorated the target dose coverage. Tumor volume changes before treatment may predict changes during treatment. Abstract: Objective: To study the impact of target volume changes in brain metastases during fractionated stereotactic radiosurgery (fSRS) and identify patients that benefit from MRI guidance. Material and methods: For 15 patients (18 lesions) receiving fSRS only (fSRSonly ) and 19 patients (20 lesions) receiving fSRS postoperatively (fSRSpostop ), a treatment planning MRI (MR0) and repeated MRI during treatment (MR1) were acquired. The impact of target volume changes on the target coverage was analyzed by evaluating the planned dose distribution (based on MR0) on the planning target volume (PTV) during treatment as defined on MR1. The predictive value of target volume changes before treatment (using the diagnostic MRI (MRD)) was studied to identify patients that experienced the largest changes during treatment. Results: Target volume changes during fSRS did result in large declines of the PTV dose coverage up to −34.8% (median = 3.2%) for fSRSonly patients. For fSRSpostop the variation and declines were smaller (median PTV dose coverage change = −0.5% (−4.5% to 1.9%)). Target volumes changes did also impact the minimum dose in the PTV (fSRSonly ; −2.7 Gy (−16.5 to 2.3 Gy), fSRSpostop ; −0.4 Gy (−4.2 to 2.5 Gy)). Changes in target volume before treatment (i.e. seen between the MRD and MR0) predicted which patients experienced the largest dose coverage declines during treatment. Conclusion: Target volume changes in brain metastases during fSRS can result in worsening of the target dose coverage. Patients benefiting the most from a repeated MRI during treatment could be identified before treatment.